Effects of poor business enabling environments on the organic value chain in Zimbabwe: the case of Hwedza organic farmers association - Muungani, Fadzai (Midlands State University, 2017)
Agriculture forms the backbone of most African economies and as such it is subject to experimentation in a bid to improve it and gain more from it. The agricultural trajectory has an element of universalism despite its settings and this normally proves consequential to the developing countries as some of the elements that make up its trajectory are not supported by other underlying reasons. It is the element of agricultural universalism that had most African countries adopt the Green Revolution and it is this very same reason that has perpetuated the adoption of the holistic approach to agriculture known as Organic farming. Since the mainstream idea is growth for farmers defined economically and general development that leads sustainability of livelihoods, it is no surprise that a systematic channel was incorporated into organic farming to achieve it. The Organic Value Chain is the systematic channel for growth within smallholder farmers and how it is governed and the milieu supporting and promoting its existence has a bearing on how things turn out for smallholder livelihoods and rural development in its entirety. HOFA was used as a case study to recognize and examine the role played by enabling environments and the players within them in impeding smallholder success through OVCs in Zimbabwe.